Penguatan Daya Saing UMKM melalui Pelatihan Manajemen Kualitas - Saragih, Susanti; Nur, Nur; Junita, Imelda; Kristine, Fanny; Mariana, Ana; Widiastuti, Ratna; Lu, Cen (Penerbit Goodwood, 2024)
Purpose: This community service activity aims to help SMEs to understand the concept and practice of product/service quality management. This topic is important because the sustainability and growth of enterprises can be created through strategic quality management activities. There are 22 SMEs in Sadang Serang, Bandung, Indonesia is involved in this activity. Method: The service-learning method was conducted through surveys, training, and evaluations. Results: The results of this activity were measured in four aspects: reaction, learning, behavior, and results. Participants provided positive feedback. This can be seen from the start of the registration until the completion of the activity. Participants also gained enhanced knowledge of the concepts shown in the pre-test and post-test scores. Participant enthusiasm can also be seen in their engagement in discussions and willingness to ask questions. Ten days after the training activity, they were surveyed to determine their behavioral changes. It was found that 50% of participants created standard operating procedures/SOPs after taking training. Limitations: Community service activities are conducted only through training. We were unable to conduct further activities, such as visits, due to time and energy constraints. After the training, only an online survey was used as a follow-up activity. Contributions: Quality management provides SMEs with a competitive advantage. This community service activity is expected to solve community problems and support SMEs in strengthening the business ecosystem around it and boosting Indonesian economic growth.